Enhancing Students' Collaborative Problem Solving Competency through Creativity-Based Learning Combined with Collaborative Learning in Chemistry Learning - Thongkorn, Patcharabhorn; Cojorn, Kanyarat (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2025)
In an era demanding teamwork and innovation,collaborative problem-solving (CPS) equips students to negotiate diverse perspectives, co-construct knowledge, and tackle complex real-world challenges. This action research study investigated the effectiveness of Creativity-Based Learning (CBL) combined with Collaborative Learning (CL) in developing collaborative problem-solving (CPS) competencies among 18 Grade 10 students in a chemistry unit on Solutions. Conducted over three iterative cycles, the research employed a mixed-methods approach, collecting data through: (1) nine CBL-CL lesson plans, (2) a CPS competency assessment, (3) structured observations of student behaviors, and (4) semi-structured interviews. Quantitative analysis (means, percentages) of assessment scores revealed progressive improvement: 27.8% (5 students) met the high CPS standard in Cycle 1, increasing to 44.4% (8 students) in Cycle 2, and 88.9% (16 students) in Cycle 3. Qualitative findings from observations and interviews highlighted enhanced engagement, communication, and creative problem-solving strategies. The study demonstrates that CBL-CL significantly strengthens CPS skills in science education. Recommendations include integrating CBL-CL into broader curricula, teacher training on facilitation techniques, and extended implementation periods for sustained competency development.